Discovery of novel polyamide-pyrrolobenzodiazepine hybrids for antibody-drug conjugates. (15th September 2022) - Thomas, Joshua D.; Yurkovetskiy, Aleksandr V.; Yin, Mao; Bodyak, Natalya D.; Gumerov, Dmitry R.; Tang, Shuyi; Kelleher, Eoin; Jones, Brian D.; Protopopova, Marina; Qin, LiuLiang; Uttard, Alex; Demady, Damon R.; et al.
Graphical abstract: Abstract: Pyrrolobenzodiazepine (PBD) dimers are well-known highly potent antibody drug conjugate (ADC) payloads. The corresponding PBD monomers, in contrast, have received much less attention from the ADC community. We prepared several novel polyamide-linked PBD monomers and evaluated their utility as ADC payloads. The unconjugated polyamide-PBD hybrids exhibited potent antiproliferative activity (IC50 range: 10 −11 –10 −8 M) against a variety of HER2-expressing cancer cell lines. Several peptide-linked variants of the lead compound were prepared and conjugated to trastuzumab to afford ADCs with drug-to-antibody (DAR) ratios ranging from 3 to 5. The ADCs exhibited antigen-dependent cytotoxicity in vitro and potently suppressed tumor xenograft growth in vivo in a target-dependent manner. Moreover, the ADCs were well-tolerated in both mouse and rat. This work demonstrates for the first time that PBD polyamide hybrids can serve as effective ADC payloads.